A Band-Notched Antenna With Two Radiation Zeros Using Grounded Coplanar Waveguide Filter for 2.4/5 GHz WLAN Applications - Li, Min; Xu, Feng (Frontiers in Physics, 2021)
In this article, a band-notched dual-polarized crossed dipole antenna is proposed for 2.4/5 GHz WLAN applications. The proposed antenna works on the WLAN 2.4-GHz (2.4–2.48 GHz) and 5-GHz (5.15–5.85 GHz) bands for a VSWR <2 with two radiation zeros within 3.4–3.6 GHz. First, an ultra-wideband crossed dipole antenna with an operating frequency of 2.4–5.8 GHz is designed using the grounded coplanar waveguide (GCPW) feeding structure. Second, a miniaturized defected microstrip structure (DMS) is embedded in the GCPW feeding strip to form a stopband behavior with a radiation zero. Finally, combining with the design of a C-shaped split ring resonator (SRR) on the arms of the dipole antenna, a band notch (3.4–3.6 GHz) with two radiation zeros can be realized. These two radiation zeros can be adjusted independently to achieve a wide stopband performance. As a result, compared with the original ultra-wideband dipole antenna, the realized gains of the proposed antenna in the 3.4–3.6 GHz range are all suppressed from 8 dBi to less than −8 dBi. The proposed antenna can realize the stable unidirectional radiation pattern and a high gain of around 7 dBi in the lower band and 8.5 dBi in the higher band of WLAN. As a demonstration, the proposed antenna is fabricated and measured, and the measurement results are in good agreement with the simulation results.